2020
DOI: 10.1101/2020.07.20.20151043
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The left inferior frontal gyrus is causally involved in selective semantic retrieval: Evidence from tDCS in primary progressive aphasia

Abstract: Lesion and imaging studies have shown that the left inferior frontal gyrus (IFG) is involved in selective semantic retrieval of information from the temporal lobes. However, causal, i.e., interventional, evidence is sparse. In the present study we addressed this question by testing whether transcranial direct current stimulation (tDCS) over the left IFG in a group of individuals with primary progressive aphasia may improve semantic fluency, a task that relies to selective semantic retrieval. Semantic fluency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 80 publications
(111 reference statements)
0
1
0
Order By: Relevance
“…Although still in its advent for neurodegenerative conditions, there is promise that tDCS may augment language therapy effects in PPA, and most tDCS studies have shown near-transfer effects, i.e., generalization to untrained items [14][15][16][17][18][19]. There is also evidence that tDCS effects over the left IFG generalize to untrained but related language tasks in PPA, such as generalization of a naming intervention to an untrained verbal fluency task [20,21]; we reasoned that this occurred because both tasks involve strategic retrieval and selection of the correct word amongst alternatives. However, far-transfer tDCS effects to untrained language functions and not only tasks, are reported in two small studies that showed a generic overall improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Although still in its advent for neurodegenerative conditions, there is promise that tDCS may augment language therapy effects in PPA, and most tDCS studies have shown near-transfer effects, i.e., generalization to untrained items [14][15][16][17][18][19]. There is also evidence that tDCS effects over the left IFG generalize to untrained but related language tasks in PPA, such as generalization of a naming intervention to an untrained verbal fluency task [20,21]; we reasoned that this occurred because both tasks involve strategic retrieval and selection of the correct word amongst alternatives. However, far-transfer tDCS effects to untrained language functions and not only tasks, are reported in two small studies that showed a generic overall improvement.…”
Section: Introductionmentioning
confidence: 99%